1989
DOI: 10.1073/pnas.86.15.5815
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan fluorescence quenching as a monitor for the protein conformation changes occurring during the photocycle of bacteriorhodopsin under different perturbations.

Abstract: The step, leading to a proton-pumping process that increases the proton concentration on the outside surface of the membrane (7). The created proton gradient across the membrane is then used to transform ADP into ATP in the final step of the photosynthesis of bR (8). Thus, the understanding of the mechanism of the PSB deprotonation becomes important to our understanding of the molecular mechanism of solar energy storage in nature.bR normally contains bound Ca2' and Mg2+ (9, 10).Acidification or removal of meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…Tryptophan fluorescence quenching was used as a monitor for protein conformation changes occurring during the photocycle of bR [90]. In particular, tryptophan fluorescence changes were observed upon formation of the M-intermediate [90]. A similar result was obtained in investigations of tryptophan fluorescence changes upon formation of the MII state in visual rhodopsin [69].…”
Section: Experimental Approaches To Gain Unique Insight Into Rhodomentioning
confidence: 90%
See 1 more Smart Citation
“…Tryptophan fluorescence quenching was used as a monitor for protein conformation changes occurring during the photocycle of bR [90]. In particular, tryptophan fluorescence changes were observed upon formation of the M-intermediate [90]. A similar result was obtained in investigations of tryptophan fluorescence changes upon formation of the MII state in visual rhodopsin [69].…”
Section: Experimental Approaches To Gain Unique Insight Into Rhodomentioning
confidence: 90%
“…Tryptophan fluorescence quenching was used as a monitor for protein conformation changes occurring during the photocycle of bR [90]. In particular, tryptophan fluorescence changes were observed upon formation of the M-intermediate [90].…”
Section: Experimental Approaches To Gain Unique Insight Into Rhodomentioning
confidence: 99%
“…[40] Microfluidic chip can also be coupled with fluorescent immunoassay for Mycobacterium tuberculosis and with high-throughput LAMP analysis for aerosolized bacteria. [41,42]…”
Section: Bacteria Aerosol Sampling Followed By Culture-free Detectionmentioning
confidence: 99%
“…Upon absorption of light, the light adapted bR undergoes a photocycle that involves a number of spectroscopically distinct intermediates: bR560 -_ K610 -> L5 M42-> N520 -064-bR560 bR contains 8 tryptophan residues out of a total 248 amino acid residues in its polypeptide chain (2). The possible involvement of tryptophan residues in bR proton pumping has been studied by several different techniques (3)(4)(5)(6)(7)(8). Fluorescence quenching upon retinal binding revealed that most of tryptophans in bR interact with the retinal chromophore (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…A time-resolved fluorescence study has detected the photolysis-induced changes in the fluorescence intensity during the lifetime of L and M intermediates, indicating that some of tryptophan residues undergo a change in environment in the vicinity of the retinal chromophore (7). Furthermore, a tryptophan fluorescence quenching study of different perturbations on bR such as deionization and delipidation has shown that different protein conformation changes may occur during the photocycle of bR under these perturbations (8). Recently, it has been Tatsushi Mogi's present address is Department of Biology, Faculty of Science, University of Tokyo, Hongo, Bunkyo-ku, Tokyo 113, Japan.…”
Section: Introductionmentioning
confidence: 99%